Genetic identity in genebanks: application of the SolCAP 12K SNP array in fingerprinting and diversity analysis in the global in trust potato collection - Ellis, David; Chavez, O.; Coombs, J.; Soto, J.; Gómez, R.; Douches, D.; Panta, A.; Silvestre, R.; Anglin, Noelle L. (Canadian Science Publishing, 2018)
Breeders rely on genetic integrity of material from genebanks; however, admixture, mislabeling, and errors in original data can occur and be detrimental. Two hundred and fifty accessions, representing paired samples consisting of original mother plants and their in vitro counterparts from the cultivated potato collection at the International Potato Center (CIP) were fingerprinted using the Infinium 12K V2 Potato Array to confirm genetic identity of the accessions and evaluate genetic diversity of the potato collection. Diploid, triploid, and tetraploid accessions were included, representing seven cultivated potato taxa (based on Hawkes, 1990). Fingerprints between voucher mother plants maintained in the field and in vitro clones of the same accession were used to evaluate identity, relatedness, and ancestry using hierarchal clustering and model-based Bayesian admixture analyses. Generally, in vitro and field clones of the same accession grouped together; however, 11 (4.4%) accessions were mismatches genetically, and in some cases the SNP data revealed the identity of the mixed accession. SNP genotypes were used to assess genetic diversity and to evaluate inter- and intraspecific relationships along with determining population structure and hybrid origins. Phylogenetic analyses suggest that the triploids included in this study are genetically similar. Further, some genetic redundancies among individual accessions were also identified along with some putative misclassified accessions. Accessions generally clustered together based on taxonomic classification and ploidy level with some deviations. STRUCTURE analysis identified six populations with significant gene flow among the populations, as well as revealed hybrid taxa and accessions. Overall, the Infinium 12K V2 Potato Array proved useful in confirming identity and highlighting the diversity in this subset of the CIP collection, providing new insights into the accessions evaluated. This study provides a model for genetic identity of plant genetic resources collections as mistakes in conservation of these collections and in genebanks is a reality. For breeders and other users of these collections, confirmed identity is critical, as well as for quality management programs and to provide insights into the accessions evaluated.